A dense linkage map for a large repetitive genome: discovery of the sex-determining region in hybridizing fire-bellied toads (Bombina bombina and Bombina variegata) - Nürnberger, Beate; Baird, Stuart J E; Čížková, Dagmar; Bryjová, Anna; Mudd, Austin B; Blaxter, Mark L; Szymura, Jacek M (G3 (Bethesda, Md.), 2021)
Genomic analysis of hybrid zones offers unique insights into emerging reproductive isolation and the dynamics of introgression. Because hybrid genomes consist of blocks inherited from one or the other parental taxon, linkage information is essential. In most cases, the spectrum of local ancestry tracts can be efficiently uncovered from dense linkage maps. Here, we report the development of such a map for the hybridizing toads, Bombina bombina and Bombina variegata (Anura: Bombinatoridae). Faced with the challenge of a large (7-10 Gb), repetitive genome, we set out to identify a large number of Mendelian markers in the nonrepetitive portion of the genome that report B. bombina vs B. variegata ancestry with appropriately quantified statistical support. Bait sequences for targeted enrichment were selected from a draft genome assembly, after filtering highly repetitive sequences. We developed a novel approach to infer the most likely diplotype per sample and locus from the raw read mapping data, which is robust to over-merging and obviates arbitrary filtering thresholds. Validation of the resulting map with 4755 markers underscored the large-scale synteny between Bombina and Xenopus tropicalis. By assessing the sex of late-stage F2 tadpoles from histological sections, we identified the sex-determining region in the Bombina genome to 7 cM on LG5, which is homologous to X. tropicalis chromosome 5, and inferred male heterogamety. Interestingly, chromosome 5 has been repeatedly recruited as a sex chromosome in anurans with XY sex determination.
Keywords: linkage map; population pileups diplotyping; Male; Chromosome Mapping; anurans; segregation distortion; hybrid zone; žáby; Anura; mužské pohlaví; genome assembly; Genetic Linkage; genom; targeted capture; larva; Animals; genetická vazba; mapování chromozomů; zvířata; large-scale synteny; Genome; Larva; sex-determining region